Factores que inciden en la continuación de las organizaciones empresariales familiares en la ciudad de Trujillo - La Libertad. - Escobedo Honores, Bruno Alonso (2014)
Today, over 90% of companies in our country are family enterprises (INEI, June 2013), therefore, play an important and dominant role in our economy. Clearly, all these companies have a life cycle in which the owners are constantly faced with new and unpredictable challenges that make business and family grow and mature. Few of these family businesses have survived from generation to generation, but many do not survive because of improper handling and understanding of the forces that constitute a family business (family, business and property). The main objective of this research is to conduct a presentation on the factors affecting the survival, growth and development of family businesses and possible tools to solve these problems that hinder the continuity of the company in the market. The study of these family businesses will help explain the most common problems among them the emotional and academic factors; as lack of professionalism, sense of belonging, business experience, and lack of family protocol. This seeks to provide alternative solutions that contribute to improving the situation of family enterprises in our country.